PENGARUH BRAND LOYALTY DAN DISKON TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK WARDAH PADA PLATFORM E-COMMERCE SHOPEE - Desfitriady; Desmaria Natalia Waruwu; Mursyidah, Desta Sulaesih (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2025)
The rapid growth of e-commerce in Indonesia, especially through the Shopee platform, has intensified competition in the cosmetics sector and encouraged brands like Wardah to optimize their marketing strategies. Nonetheless, initial survey findings show that consumer loyalty remains relatively low and discount programs have yet to deliver maximum impact. This study investigates the effect of brand loyalty and discounts on purchasing decisions of Wardah cosmetics on Shopee. Using a quantitative survey method, data were collected from 96 consumers in Bandung and analyzed with multiple linear regression. The findings indicate that both brand loyalty and discounts significantly influence purchasing decisions. Brand loyalty was generally perceived positively, though some weaknesses were noted in consumers’ willingness to recommend the brand. Discounts were also viewed favorably, yet require improvement in providing more consistent direct benefits. The study concludes that strengthening brand loyalty and optimizing discount strategies in an integrated manner can more effectively enhance purchasing decisions on Shopee. Keywords: Brand Loyalty; Discount; Purchasing Decisions.